State-dependent cross-brain information flow in borderline personality disorder - Bilek, Edda; Stößel, Gabriela; Schäfer, Axel; Clement, Laura; Ruf, Matthias; Robnik, Lydia; Neukel, Corinne; Tost, Heike; Kirsch, Peter; Meyer-Lindenberg, Andreas (JAMA psychiatry, 2017)
Importance: Although borderline personality disorder (BPD)—one of the most common, burdensome, and costly psychiatric conditions—is characterized by repeated interpersonal conflict and instable relationships, the neurobiological mechanism of social interactive deficits remains poorly understood. Objective: To apply recent advancements in the investigation of 2-person human social interaction to investigate interaction difficulties among people with BPD. Design, Setting, and Participants: Cross-brain information flow in BPD was examined from May 25, 2012, to December 4, 2015, in pairs of participants studied in 2 linked functional magnetic resonance imaging scanners in a university setting. Participants performed a joint attention task. Each pair included a healthy control individual (HC) and either a patient currently fulfilling DSM-IV criteria for BPD (cBPD) (n = 23), a patient in remission for 2 years or more (rBPD) (n = 17), or a second HC (n = 20). Groups were matched for age and educational level. Main Outcomes and Measures: A measure of cross-brain neural coupling was computed following previously published work to indicate synchronized flow between right temporoparietal junction networks (previously shown to host neural coupling abilities in health). This measure is derived from an independent component analysis contrasting the time courses of components between pairs of truly interacting participants compared with bootstrapped control pairs. Results: In the sample including 23 women with cBPD (mean [SD] age, 26.8 [5.7] years), 17 women with rBPD (mean [SD] age, 28.5 [4.3] years), and 80 HCs (mean [SD] age, 24.0 [3.4] years]) investigated as dyads, neural coupling was found to be associated with disorder state (η2 = 0.17; P = .007): while HC-HC pairs showed synchronized neural responses, cBPD-HC pairs exhibited significantly lower neural coupling just above permutation-based data levels (η2 = 0.16; P = .009). No difference was found between neural coupling in rBPD-HC and HC-HC pairs. The neural coupling in patients was significantly associated with childhood adversity (T= 2.3; P = .03). Conclusions and Relevance: This study provides a neural correlate for a core diagnostic and clinical feature of BPD. Results indicate that hyperscanning may deliver state-associated biomarkers for clinical social neuroscience. In addition, at least some neural deficits of BPD may be more reversible than is currently assumed for personality disorders.
Gesehen am 18.06.2018